Situational analysis on fluoroquinolones use and characterization of high-level ciprofloxacin-resistant Enterococcus faecalis by integrated broiler operations in South Korea - Lee, Yu Jin; Jung, Hye-Ri; Yoon, Sunghyun; Lim, Suk-Kyung; Lee, Young Ju (Frontiers in Veterinary Science, 2023)
Fluoroquinolones are classified as “critically important antimicrobials for human medicine”; however, their extensive use in livestock poses a significant health risk to humans as it leads to the rapid spread of antimicrobial resistance. This study confirmed that 40.0%–71.4% of the farms in three of the five integrated broiler operations were administered ciprofloxacin (CIP). Moreover, preventive purposes (60.9%), veterinarian prescriptions (82.6%), drinking water route (100%), and one to three days (82.6%) of age were significantly highest (P < 0.05). 194 high-level ciprofloxacin-resistant (HLCR) Enterococcus faecalis (E. faecalis) were found in 65 of 74 farms, and of which, the prevalence of qnrA (63.9%), tetM (60.3%), ermB (64.9%), blaz (38.7%), and catA (34.0%) was significantly highest (P < 0.05). 154 (79.4%) isolates showed MDR, and the distribution of MDR was significantly differences among the operations (P < 0.05). All HLCR E. faecalis possessed double mutations in gyrA and parC, and S83I/S80I (90.7%) mutations were most commonly identified. Interestingly, the distribution of isolates with MICs ≥ 512 for both CIP and moxifloxacin was significantly higher in CIP–administered farms (56.5%) than in non–CIP–administered farms (41.4%) (P < 0.05). Also, the prevalence of strong or moderate biofilm formers in HLCR E. faecalis was significantly higher than that of weak and no biofilm formers (P < 0.05). HLCR E. faecalis were heavily distributed in the broiler farms in Korea; therefore, it is necessary to minimize the prevalence of resistant bacteria via structural management regulations such as cleaning and disinfection of farm environments.